Đặc điểm khoáng vật học của Crompsinel trong các thành tạo siêu Mafic khối Núi Nưa (đới Sông Mã) - Niên, Bùi Ấn (Vietnam Journal of Earth Sciences, 2008)
Mineralogical characteristics of chromspinel in the mafic and ultramafic forming of Nui Nua massive (from Song Ma zone)